Dialogue in the Qur’anic Perspective and its Impact on Coexistence - Khaleel Al-Saleeh, Sedeeq (Opción, 2019)
As the title of the research explains, dialogue is much broader in scope than inter- faith or theological conversations and conferences, although these are an important (and worthwhile) dimension of it. The ‘dialogue approach’ could be thought of as a positive disposition to others being (and remaining) others which encourages the virtues of neighbor lines, friendship and mutual trust and caring. Consider dialogue as an important issue that leads to the truth, and formats the convictions which deals with the movements of the conflicts in many fields of ideas, politics and soci- ety. It is an important device for rapprochement and coexistence, and it has a great impact on the people who want to live together if controls its elements. So the Holy Quran support the principle of dialogue.